A Rapid Bacteriophage DNA Extraction Method - Jakočiūnė, Džiuginta; Moodley, Arshnee (Methods and protocols, 2018)
Bacteriophages (phages) are intensely investigated as non-antibiotic alternatives to circumvent antibiotic resistance development as well as last resort therapeutic options against antibiotic resistant bacteria. As part of gaining a better understanding of phages and to determine if phages harbor putative virulence factors, whole genome sequencing is used, for which good quality phage DNA is needed. Traditional phage DNA extraction methods are tedious and time consuming, requiring specialized equipment e.g., an ultra-centrifuge. Here, we describe a quick and simple method (under four hours) to extract DNA from double stranded DNA (dsDNA) phages at titers above 1.0 × 1010 plaque-forming units (PFU)/mL. This DNA was suitable for library preparation using the Nextera XT kit and sequencing on the Illumina MiSeq platform.